Leishmania donovani Isolates with Antimony-Resistant but Not -Sensitive Phenotype Inhibit Sodium Antimony Gluconate-Induced Dendritic Cell Activation - Haldar, Arun Kumar (Public Library of Science, 2010)
The inability of sodium antimony gluconate (SAG)-unresponsive kala-azar patients to clear Leishmania donovani (LD) infection despite SAG therapy is partly due to an ill-defined immune-dysfunction. Since dendritic cells (DCs) typically initiate anti-leishmanial immunity, a role for DCs in aberrant LD clearance was investigated. Accordingly, regulation of SAG-induced activation of murine DCs following infection with LD isolates exhibiting two distinct phenotypes such as antimony-resistant (Sb(R)LD) and antimony-sensitive (Sb(S)LD) was compared in vitro. Unlike Sb(S)LD, infection of DCs with Sb(R)LD induced more IL-10 production and inhibited SAG-induced secretion of proinflammatory cytokines, up-regulation of co-stimulatory molecules and leishmanicidal effects. Sb(R)LD inhibited these effects of SAG by blocking activation of PI3K/AKT and NF-κB pathways. In contrast, Sb(S)LD failed to block activation of SAG (20 µg/ml)-induced PI3K/AKT pathway; which continued to stimulate NF-κB signaling, induce leishmanicidal effects and promote DC activation. Notably, prolonged incubation of DCs with Sb(S)LD also inhibited SAG (20 µg/ml)-induced activation of PI3K/AKT and NF-κB pathways and leishmanicidal effects, which was restored by increasing the dose of SAG to 40 µg/ml. In contrast, Sb(R)LD inhibited these SAG-induced events regardless of duration of DC exposure to Sb(R)LD or dose of SAG. Interestingly, the inhibitory effects of isogenic Sb(S)LD expressing ATP-binding cassette (ABC) transporter MRPA on SAG-induced leishmanicidal effects mimicked that of Sb(R)LD to some extent, although antimony resistance in clinical LD isolates is known to be multifactorial. Furthermore, NF-κB was found to transcriptionally regulate expression of murine γglutamylcysteine synthetase heavy-chain (mγGCS(hc)) gene, presumably an important regulator of antimony resistance. Importantly, Sb(R)LD but not Sb(S)LD blocked SAG-induced mγGCS expression in DCs by preventing NF-κB binding to the mγGCS(hc) promoter. Our findings demonstrate that Sb(R)LD but not Sb(S)LD prevents SAG-induced DC activation by suppressing a PI3K-dependent NF-κB pathway and provide the evidence for differential host-pathogen interaction mediated by Sb(R)LD and Sb(S)LD.